Touristic activity and disturbances over Nearctic migratory birds oin the coast of Piauí State, Brazil - Siqueira, Airton Janes da Silva; Nascimento, Muryllo dos Santos; Santos, Suely Silva; Guzzi, Anderson; Braga, Solano de Souza (Sociedade & Natureza, 2024)
The migration of birds is a phenomenon that leads thousands of individuals to move between different areas for feeding and breeding, with these movements often crossing geopolitical borders. This behavior is crucial for the survival of many species. However, anthropogenic impacts are affecting the habitats of these species, contributing to the decline in bird populations. In light of this, the aim of this study was to analyze the disturbances caused by tourist activities on migratory birds visiting the estuaries of the Cardoso and Camurupim rivers on the coast of the state of Piauí and propose measures to mitigate disturbances on the birds. Samples were taken at three observation points, where changes in bird behavior in response to tourist activities were analyzed. Binoculars, a photographic camera, and a laser rangefinder were used to assist in delineating impact zones. Although various tourist activities occur in the region, the main disturbances are caused by kitesurfing and tourists walking near the feeding or resting areas of the species. Calidris minutilla, Calidris pusilla, Calidris alba, Actitis macularius, and Charadriius semipalmatus were the least sensitive species to disturbances, reacting more frequently within impact zones Z = 0-30m and Z = 30-60m, while the species Pluvialis squatarola, Numenius hudsonicus, Tringa melanoleuca, Calidris canutus, Limnodromus griseus, and Pandion haliaetus showed greater escape distances. The results of this study show that tourists walking and kitesurfing are the main activities impacting migratory birds in the region, highlighting the need for measures to mitigate such impacts. Based on the results, the creation of minimum protection zones of 160m and 200m is recommended to mitigate disturbances caused by the approach of bathers and kitesurfers.